Ionospheric variability studies in Argentina - Ezquer, Rodolfo Gerardo (2007)
This paper reviews and extends studies on ionospheric variability performed by the Argentine scientific community. Ground based ionosonde measurements for different seasonal and solar conditions and vertical total electron content (VTEC) obtained with GPS satellite signals during a high solar activity year are used. Median, quartiles and deciles are used to specify the variability. In general, the results show that: (a) the variability is higher in low solar activity than in high solar activity, and (b) it is larger by night than by day. Moreover, is shown that could be possible specify the variability of foF2 for high solar activity and hours around noon.